The Effect of Problem Solving Style According to Positive Motivation On The Performance of Volleyball Skills In Preparatory Schools Students - ALANI, ABDULRAHMAN MAJEED; Jasem , Wasan (Journal of Physical Education, 2023)
The importance of research lies in designing teaching units based on problem solving according to positive motivation for learning performance of some fundamental volleyball skills as well as identifying the effect of this style on learning volleyball skills (serving, underhand and overhead passing). The researchers used the experimental method on (198) students from Al Ameen preparatory school for the academic year 2022 – 2023. Twenty four students were divided into two equal groups; 12 students from section A to form the experimental group and 12 students from section c to form the controlling group. Pretests were conducted followed by the style applied on the students and posttests. The data was collected and treated using proper statistical operations to conclude that problem solving style have a positive role in achieving significant results for experimental group as well as its role in individual differences among students. Finally the researchers recommended the necessity of using this style in learning and making similar studies using this style on other subjects and other skills.